(:unas) unassigned - Georgiou, Anastasios M. (My University, 2018)
A Bihemispheric Theta Burst Stimulation (TBS) approach to improve language performance in a case of chronic post-stroke aphasia. Poster session to be presented at the 10th European Congress of Speech and Language Therapy. Effectiveness, Speech and Language Therapy, Science, Practice.